Beliefs about medicines and non-adherence in patients with stroke, diabetes mellitus and rheumatoid arthritis: a cross-sectional study in China. Issue 10 (5th October 2017) - Wei, Li; Champman, Sarah; Li, Xiaomei; Li, Xin; Li, Sumei; Chen, Ruoling; Bo, Nie; Chater, Angel; Horne, Robert
Abstract : Objectives: To investigate beliefs about medicines and their association with medicine adherence in patients with chronic diseases in China. Design: A cross-sectional questionnaire-based study Setting: Two large urban hospitals in Hefei and Tianjin, China Participants: Hospital inpatients (313 stroke patients) and outpatients (315 diabetic patients and 339 rheumatoid arthritis (RA) patients) were recruited between January 2014 and September 2014. Outcome measures: The Beliefs about Medicines Questionnaire (BMQ), assessing patients' beliefs about the specific medicine (Specific-Necessity and Specific-Concerns) prescribed for their conditions (stroke/diabetes/RA) and more general background beliefs about pharmaceuticals as a class of treatment (BMQ-General Benefit, Harm and Overuse); the Perceived Sensitivity to Medicines scale (PSM) assessed patients' beliefs about how sensitive they were to the effects of medicines and the Medication Adherence Report Scale. The association between non-adherence and beliefs about medicines was assessed using a logistic regression model. Results: Patients with diabetes mellitus had a stronger perceived need for treatment (mean (SD) Specific-Necessity score, 3.75 (0.40)) than patients with stroke (3.69 (0.53)) and RA (3.66 (0.44)) (p=0.049). Moderate correlations were observed between Specific-Concerns and General-Overuse, General-Harm and PSM (Pearson correlation coefficients, 0.39, 0.49 and 0.49, respectively, p<0.01). Three hundred and eleven patients were non-adherent to their medicine (159 (51.0%) in the stroke group, 60 (26.7%) in the diabetes mellitus group and 62 (19.8%) in the RA group, p<0.01). Across the whole sample, after adjusting for demographic characteristics, non-adherence was associated with patients who had higher concerns about their medicines (OR, 1.35, 95% CI 1.07 to 1.71) and patients who believed that they were personally sensitive to the effects of medications (OR 1.44, 95% CI 1.16 to 1.85). Conclusion: The BMQ is a useful tool to identify patients at risk of non-adherence. In the future, adherence intervention studies may use the BMQ to screen for patients who are at risk of non-adherence and to map interventional support.